From Model Organisms to Humans, the Opportunity for More Rigor in Methodologic and Statistical Analysis, Design, and Interpretation of Aging and Senescence Research. Issue 11 (24th December 2021) - Chusyd, Daniella E; Austad, Steven N; Brown, Andrew W; Chen, Xiwei; Dickinson, Stephanie L; Ejima, Keisuke; Fluharty, David; Golzarri-Arroyo, Lilian; Holden, Richard; Jamshidi-Naeini, Yasaman; Landsittel, Doug; Lartey, Stella; et al.
Abstract: This review identifies frequent design and analysis errors in aging and senescence research and discusses best practices in study design, statistical methods, analyses, and interpretation. Recommendations are offered for how to avoid these problems. The following issues are addressed: (a) errors in randomization, (b) errors related to testing within-group instead of between-group differences, (c) failing to account for clustering, (d) failing to consider interference effects, (e) standardizing metrics of effect size, (f) maximum life-span testing, (g) testing for effects beyond the mean, (h) tests for power and sample size, (i) compression of morbidity versus survival curve squaring, and (j) other hot topics, including modeling high-dimensional data and complex relationships and assessing model assumptions and biases. We hope that bringing increased awareness of these topics to the scientific community will emphasize the importance of employing sound statistical practices in all aspects of aging and senescence research.